2007
DOI: 10.1080/10170660709509030
|View full text |Cite
|
Sign up to set email alerts
|

A Label-Correcting Tracing Algorithm for the Approximation of the Probability Distribution Function of the Project Completion Time

Abstract: When facing projects with uncertain factors, most of the project managers are interested to secure the pdf of the completion time of the project so as to have full insights into its randomness. For large-size SAN with general types of pdf for the duration of activities, the project managers must turn to the techniques of discretization since the other approaches in the literature become too demanding in computational loading. In this study, we find that there are two problems when applying the techniques of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the classical NPV method, the financial managers tend to use point input prices, implicitly assuming that these prices are predictable, and they usually incorporate the uncertainty in the field of capital budgeting analysis based on intuitive method or probabilistic approach. However, these common methods still have the disadvantages of requiring the fulfillment of some assumptions for probabilistic distributions and relying on point estimation to obtain these uncertain parameters [30]. Kahraman, Ruan, and Tolga [11] indicated that in an uncertain economic decision environment, an expert's knowledge about the cash flows and the capital costs consists of lot of vagueness instead of randomness.…”
Section: The Disadvantage Of Classical Npv Methodsmentioning
confidence: 99%
“…In the classical NPV method, the financial managers tend to use point input prices, implicitly assuming that these prices are predictable, and they usually incorporate the uncertainty in the field of capital budgeting analysis based on intuitive method or probabilistic approach. However, these common methods still have the disadvantages of requiring the fulfillment of some assumptions for probabilistic distributions and relying on point estimation to obtain these uncertain parameters [30]. Kahraman, Ruan, and Tolga [11] indicated that in an uncertain economic decision environment, an expert's knowledge about the cash flows and the capital costs consists of lot of vagueness instead of randomness.…”
Section: The Disadvantage Of Classical Npv Methodsmentioning
confidence: 99%